THE DENSITY OF BENTHIC ORGANISMS IN PEAT SOIL MEDIA WITH DIFFERENT VERMICOMPOST - Mustafa Kamal; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstrackThis study was conducted from February-March 2017, at the Kualu Nenas Village, Tambang District, Kampar Regency, Riau Province. The objective of this research was to determine the best type of vermicompost to increase the density of benthic organisms on peat soil media. The research method was an experiment using a Completely Randomized Design (CRD) with 4 treatment levels and 3 replications. The treatments used were P0 (control / without vermicompost); P1 (human fecal vermicompost) P2 (cow fecal vermicompost) P3 (chicken fecal vermicompost). Results showed that the best treatment was P1 vermicompost human fecal. The density of was macrozoobenthos as 6,368 ind m-2 and mikrozoobenthos was 12,956 ind  m-2. Water quality such as temperature was 27-320C, pH 3,6-6,8, Oxygen dissolved 2,9-6,0 mg  L-1, nitrate 5,253-14,059 ppm and Orthophosphate 3,434-8,915 ppm. Keywords: Vermicompost, Macrozoobenthos, Microzoobenthos, Abundance of    Macrozoobenthos and abundance of Microzoobenthos